Digitalisasi Perpajakan dan Pengetahuan Pajak dalam Meningkatkan Kepatuhan Wajib Pajak UMKM Semarang - Riskita Salsabilla Ayumida; Eni Endaryati (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
his study aims to analyze the effect of tax knowledge and digital tax access on MSME taxpayer compliance in Semarang City. The study is motivated by the low level of MSME tax compliance amid the increasing implementation of digital taxation services such as e-Filing, e-Billing, e-Faktur, e-Bupot, and Coretax. This study used a quantitative approach with a survey method involving 100 MSME respondents selected through purposive sampling. Data were collected using Likert-scale questionnaires and analyzed using multiple linear regression. The results show that tax knowledge and ease of digital tax access have a positive and significant effect on MSME taxpayer compliance, both partially and simultaneously. Ease of digital tax access was found to be the dominant factor influencing compliance. The novelty of this study lies in integrating tax knowledge and digital tax access in explaining MSME taxpayer compliance in the context of taxation digitalization. This study contributes empirical evidence regarding the importance of tax literacy and digital tax services. The theoretical implication strengthens the Theory of Planned Behavior in explaining taxpayer compliance behavior.